2008
DOI: 10.1614/ws-08-064.1
|View full text |Cite
|
Sign up to set email alerts
|

Exudation of Mesotrione from Potato Roots Injures Neighboring Plants

Abstract: Mesotrione is an effective herbicide for volunteer potato control but is not selective in several crops, including onion and carrot. Studies were conducted in 2006 to evaluate the effectiveness of wiper-applied mesotrione for control of volunteer potato in a potato crop. Surprisingly, nontreated potatoes growing adjacent to mesotrione-treated plants exhibited bleaching symptoms resembling mesotrione injury. Additional field trials confirmed injury to nontreated plants growing within 26 cm of potatoes treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Sequential mesotrione applications caused greater visual injury and density reductions than did single applications (Table 5), so reductions in rhizome growth during the year of application are plausible and should be measured in future research. Boydston and Al-Khatib (2008) also reported that up to 15% of foliar-applied mesotrione was translocated to developing roots and tubers of potato. Sequential mesotrione applications to goldenrods may therefore increase the amount of mesotrione translocated to roots and rhizomes, likely contributing to the increased control observed in the bearing year.…”
Section: Effect Of Sequential Mesotrione Applications On Goldenrodmentioning
confidence: 96%
See 1 more Smart Citation
“…Sequential mesotrione applications caused greater visual injury and density reductions than did single applications (Table 5), so reductions in rhizome growth during the year of application are plausible and should be measured in future research. Boydston and Al-Khatib (2008) also reported that up to 15% of foliar-applied mesotrione was translocated to developing roots and tubers of potato. Sequential mesotrione applications to goldenrods may therefore increase the amount of mesotrione translocated to roots and rhizomes, likely contributing to the increased control observed in the bearing year.…”
Section: Effect Of Sequential Mesotrione Applications On Goldenrodmentioning
confidence: 96%
“…Glufosinate generally provides variable control of established perennial weeds (Bradley and Hagood 2002;Nelson et al 2002;Pline et al 2000) but does exhibit phloem mobility and translocation to roots in some weed species (Pline et al 1999;Steckel et al 1997) that may have contributed to additional rhizome injury when used as a spot application. Root translocation of mesotrione can also occur (Boydston and Al-Khatib 2008), suggesting this herbicide may have also caused damage to rhizomes. Reductions in bearing-year shoot density after spot applications also indicate spot applications of mesotrione are more effective than single broadcast applications (Tables 5 and 6), likely due to improved coverage of target plants with spot applications relative to broadcast applications.…”
Section: Evaluation Of Summer Herbicide Spot Applicationsmentioning
confidence: 99%
“…Among these, root exudates are well known to act as chemical defense mechanisms to protect border cells and respond to possible infections (Baetz and Martinola 2014). Herbicides, when applied to susceptible and non-susceptible plants, may alter or become a component of root exudates (Barker and Dayan 2019;Boydston and Al-Khatib 2008;Dinelli et al 2007;Hickman et al 1989;Kremer et al 2005). Studies of herbicide translocation of pyridine carboxylic acids have indicated that the distribution variability of herbicides to roots and other plant parts is wide, and the compounds are not metabolized within the plants (Bukun et al 2009;Lewis et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of herbicide translocation of pyridine carboxylic acids have indicated that the distribution variability of herbicides to roots and other plant parts is wide, and the compounds are not metabolized within the plants (Bukun et al 2009;Lewis et al 2013). When released from treated plants, root exudates may have the potential to cause non-target impacts to species that are sensitive to the applied herbicide (Boydston and Al-Khatib 2008;Dinelli et al 2007;Hickman et al 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation